Trade competitiveness diagnostic toolkit - Reis, José Guilherme Almeida dos (Trade and development series., 2012)
This toolkit provides a framework, guidelines, and practical tools for conducting an analysis of a country's trade competitiveness in terms of growth and share performance, diversification, and quality. It aims to facilitate the identification of the main constraints to improved trade competitiveness and the policy responses to overcome these constraints.